Longitudinal structural and functional brain network alterations in a mouse model of neuropathic pain - Bilbao, Ainhoa; Becker, Robert; Singaravelu, Sathish Kumar; Sack, Markus; Sartorius, Alexander; Spanagel, Rainer; Weber-Fahr, Wolfgang (Neuroscience, 2018)
Neuropathic pain affects multiple brain functions, including motivational processing. However, little is known about the structural and functional brain changes involved in the transition from an acute to a chronic pain state. Here we combined behavioral phenotyping of pain thresholds with multimodal neuroimaging to longitudinally monitor changes in brain metabolism, structure and connectivity using the spared nerve injury (SNI) mouse model of chronic neuropathic pain. We investigated stimulus-evoked pain responses prior to SNI surgery, and one and twelve weeks following surgery. A progressive development and potentiation of stimulus-evoked pain responses (cold and mechanical allodynia) were detected during the course of pain chronification. Voxel-based morphometry demonstrated striking decreases in volume following pain induction in all brain sites assessed – an effect that reversed over time. Similarly, all global and local network changes that occurred following pain induction disappeared over time, with two notable exceptions: the nucleus accumbens, which played a more dominant role in the global network in a chronic pain state and the prefrontal cortex and hippocampus, which showed lower connectivity. These changes in connectivity were accompanied by enhanced glutamate levels in the hippocampus, but not in the prefrontal cortex. We suggest that hippocampal hyperexcitability may contribute to alterations in synaptic plasticity within the nucleus accumbens, and to pain chronification.
Gesehen am 23.08.2019